2018
DOI: 10.3389/fpls.2018.01354
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of TpNRAMP3, a Metal Transporter From Polish Wheat (Triticum polonicum L.)

Abstract: Essential transition metals and non-essential metals often co-exist in arable soils. In plants, some transition metal transporters, such as the natural resistance-associated macrophage proteins (NRAMPs), poorly selectively transport metals with similar chemical properties whether they are essential or non-essential. In this study, a member of the NRAMP transporter family, TpNRAMP3, was identified from dwarf Polish wheat (Triticum polonicum L.). TpNRAMP3 encodes a plasma membrane-localized protein and was highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The OsNRAMP1 and OsNRAMP5 iron transporters have been described as Cd influx transporters in the plasma membrane [27]. AtNRAMP6 is an intracellular transporter of metals such as Cd [28].…”
Section: Transporters Involved In CD Entry Into the Rootsmentioning
confidence: 99%
“…The OsNRAMP1 and OsNRAMP5 iron transporters have been described as Cd influx transporters in the plasma membrane [27]. AtNRAMP6 is an intracellular transporter of metals such as Cd [28].…”
Section: Transporters Involved In CD Entry Into the Rootsmentioning
confidence: 99%
“…Transformants were selected for uracil prototrophy on yeast nitrogen base drop-out medium lacking uracil (SD-Ura) (Sigma, Missouri, USA) and by colony PCR using primer pairs speci c to each TpIRT1 homoeolog. Functional complementation assays were performed on a solid or liquid SD-Ura media as described by Peng et al (2018a) with minor modi cation for the concentration of mineral elements Cd (0 µM and 40 µM), Zn (0 µM and 4 mM), and Co (0 µM and 250 µM). For the functional complementation assays in a liquid medium, the single yeast colony was selected and grown overnight in SD-Ura liquid medium.…”
Section: Functional Complementation Assays In Saccharomyces Cerevisiaementioning
confidence: 99%
“…Due to similar chemical properties of essential mineral elements and not essential HMs, some of the MTs such as Natural Resistance-associated Macrophage Proteins (NRAMPs) transport them to upper plant parts. In dwarf polish wheat (T. polonicum), TpNRAMP3, a member of NRAMPs family was identified that is responsive for PM localized protein and it is expressed higher in leaf blades, roots and first note at jointing, booting and grain filling stages, respectively [21]. In detail, TpNRAMP3 was cloned and transformed into yeast and Arabidopsis.…”
Section: Hms Stressmentioning
confidence: 99%
“…Over-expression of TaZnF in A. thaliana significantly increased tolerance to heat and cold stress as well as promotes early flowering [16]. Similarly, there are numerous studied in many plant species evidenced the pivotal role of MTs in uptake, sequestration, translocation and detoxification of toxic HMs including cadmium (Cd) [17], chromium (Cr) [18], lead (Pb) [19], As [20], cobalt (Co) and zinc (Zn) [21], for more detail see section 3.…”
Section: Introductionmentioning
confidence: 99%